Training report: capacity building in agronomic practices, waxing and relative humidity storage technologies for shelf-life extension of fresh cassava roots. - Nyamutoka, P.; Wanda, K.; Aceng, S.; Muyinza, H.; Kaliisa, R.; Menya, G.; Nuwamanya, E.; Nyakaisiki, E.; Nanyondo, R.; Abass, A.; Matovu, Moses (2016)
This report describes the capacity building process and activities that were done to enable the value chain actors adopt and adapt the pre-and post-harvest practices, and waxing and high relative humidity storage technologies in order to run a successful business enterprise .